Estimation of humural immune response on the rabbits that immunizing with Hydatid cyst antigens by using IHAT and ElISA. - Edan, Ekhlas M.; Ardalan, Naksheen M. (Journal of the Faculty of Medicine Baghdad, 2009)
Background: Hydatid disease also known as echinococcosis or hydatidosis , is caused by infection with larva (metacestoide) of tape worms of the genus Echinococcus. Materials and methods: Twelve Rabbits were immunized with three types of antigens (Hydatid cyst fluid antigen; Protoscoleces antigen and Germinal and Laminated layer antigen) according to a specific immunization program and we used indirect hemagglutination test( IHAT) and Enzyme Linked Immuno Sorbent Assay(ELISA) for detecting the anti-Echinococcus antigens in the serum of these animals. Results: The highest titter of antibodies were recorded in the Rabbit serum when use the first antigen (Hydatid cyst fluid) by using IHA method (1:64)after the end of immunization program while in ELISA method reached (1:128), The serum level for the rabbit serum that immunization with the second antigen(Protoscoleces) has reached (1:256) by using IHAT and (1:512)when use ELISA, The highest titter of third antigen (Germinal and Laminated layer)has reached (1:128) by using IHAT and (1:256) when we used ELISA method. Conclusion: The highest antibodies titer could be found when use the Protoscoleces antigen more than Cyst fluid and Germinal and Laminated layer antigen.